A new and promising C-phycocyanin-producing cyanobacterial strain, Cyanobium sp. MMK01: practical strategy towards developing a methodology to achieve C-phycocyanin with ultra-high purity - Shafiei, Melika; Shafiei, Maral; Mohseni Sani, Naeema; Guo, Wangbiao; Guo, Shuaiqi; Vali, Hojatollah; Akbari Noghabi, Kambiz (Frontiers in Microbiology, 2024)
Selecting a suitable cyanobacterial strain and developing easy-to-afford purification processes are two crucial aspects impacting the optimal production yield and appropriate purity of C-phycocyanin (C-PC). Cyanobium sp. MMK01, a highly efficient C-PC-producing bacterium, was identified among four cyanobacterial isolates using morphological characteristics and 16S rRNA gene sequencing. The purification process of C-PC began with ammonium sulfate precipitation, leading to a purity index (PI) of 4.04. Subsequent purification through ion exchange chromatography ultimately resulted in an ultra-highly purified form of C-PC with a significant PI of 5.82. SDS-PAGE analysis of purified C-PC showed the presence of two distinct bands, α (13 kDa) and β (15 kDa). Significantly effective at scavenging free radicals, C-PC also inhibits the viability of human lung cancer cells (Calu-6). Antibacterial, anti-inflammatory, antioxidant, and cancer-preventive compounds were detected in the MMK01 cells’ methanolic extract following GC–MS analysis. The promising results indicate that Cyanobium sp. MMK01 has a great deal of potential for producing C-PC that is on par with strains found in the market, and the tried-and-true two-step purification process proved to work well to achieve an ultra-highly purified form of C-PC.